Team building an exercise in leadership - Maddux, Robert B. (Better management skills., 1994)
Team building is an essential skill for today's managers. The ability of staff to perform as a team as well as on an individual level is vitally important for the good of the department, as well as that of the whole organisation. In order to build a cohesive team that is motivated towards common goals, managers need to develop a positive attitude and adopt a structured approach to leadership. Managers who adopt these skills will find that their team members achieve more and that the workplace becomes more efficient and productive. With checklists, quizzes and examples, this self-help book provides busy managers and their teams with advice for developing and improving: planning and organisation; communication; training and coaching; the selection of qualified people; commitment and trust; and, the resolution of conflict and complaints. For managers keen to learn and improve these crucial skills, this informal step-by-step guide provides the keys to setting realistic goals and giving ongoing support and encouragement to their staff.